Authentic leadership and its impact on extra role behaviour of nurses: The mediating role of psychological capital and the moderating role of autonomy. Issue 2 (6th March 2017) - Malik, Nishtha; Dhar, Rajib Lochan
Abstract : Purpose: The purpose of this paper is to examine the relationship between authentic leadership (AL) and employee extra role behaviour (ERB) while determining the mediating effect of psychological capital (PC) and moderating effect of autonomy on that relationship. Design/methodology/approach: Data were collected from 42 small- and medium-sized hospitals in the state of Uttarakhand, India. The sample for the study included 520 nurses and their 163 supervisors. Process macro (Hayes) was used to examine the mediating role of PC and the moderating role of autonomy in the relationship between AL and ERB. Findings: Results indicate that AL is positively linked to ERB of followers. Further, PC was found to mediate the relationship between AL and ERB while autonomy acted as a moderator between PC and ERB. Practical implications: Findings of the study would help hospital managements understand the importance of technical and behavioural training of nursing staff and supervisors. The paper draws the attention of hospital administrators towards the need for formulating policies that are less restrictive and allow for greater autonomy to the nursing staff. Further, this study highlights the importance of an effective leadership approach like AL in service-oriented organizations such as healthcare institutions. Originality/value: This study contributes to existing research on AL and ERB by showing that PC and autonomy are important and relevant variables that affect the degree of influence that AL has on employee ERB.